Effect of Microstructure on Soluble Properties of Transparent Polypropylene Copolymers. (21st November 2019) - Tang, Yujing; Ren, Minqiao; Hou, Liping; Sheng, Jianfang; Guo, Meifang; Shi, Hongwei; Wang, Liangshi; Qiao, Jinliang
Abstract: Synthesis of transparent polypropylene (PP) copolymers with low migration of soluble contents is of great significance due to their extensive use in food and medicine industries. We present here a systematical study on the relationship between the microstructure of PP copolymers and their soluble properties using a solvent gradient fractionation (SGF) method. Two sets of poly(propylene- co -1-butene) (PPBu) and poly(propylene- co -ethylene) (PPEt) samples with comparable comonomer content and molecular weight were first fractionated and characterized by 13 C NMR, GPC, DSC, and WAXD. It was found that PPBu contained much less room temperature soluble fraction than PPEt because of the incorporation of 1-butene into higher molecular weight fraction than that of ethylene. The melting temperature of PPBu was found higher than that of PPEt with similar comonomer content because of the isomorphism phenomenon demonstrated by the expansion of the unit cell. The findings in this study suggest that tuning the two structure-related factors, namely, comonomer distribution homogeneity and isomorphism phenomenon, plays a key role to maintain low soluble contents of transparent PP copolymers. Graphical abstract: The effect chain structure (a) and condensed structure (b) on soluble properties of transparent polypropylene copolymers. Image 1 Highlights: This is the first report on the fractionation of PPBu using the SGF method. New insights into how the microstructure of transparent PP affects their soluble properties. The migration value of transparent PPBu can be further reduced by using high-performance catalysts.